2003
DOI: 10.1038/sj.npp.1300371
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Analysis of the Prefrontal Cortex, Amygdala, and Hippocampus in Major Depression

Abstract: Magnetic resonance imaging (MRI) studies in depressed subjects report smaller volumes of amygdala, hippocampus, inferior anterior cingulate, and the orbital prefrontal cortex (OPFC), components of the limbic-cortico-thalamic circuit. Major depression occurs more commonly in women, raising the possibility of an additional psychopathological process affecting women and not men. We sought to determine whether volumetric differences related to mood disorders are dependent on sex. Eight male and 10 female depressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
199
2
14

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(222 citation statements)
references
References 48 publications
7
199
2
14
Order By: Relevance
“…Exaggerated amygdala activation has been suggested to represent a common neurobiological pathway for stress-related disorders, such as depression and anxiety disorders (Drevets et al 2008;Etkin and Wager 2007). Likewise, in the majority of studies, larger amygdala volumes have been observed in depression (Altshuler et al 1998;Bremner et al 2000;Lange and Irle 2004;Tebartz van Elst et al 1999;van Eijndhoven et al 2009;Vassilopoulou et al 2013), (but see Hastings et al 2004;von Gunten et al 2000 for opposite findings) and PTSD (Kuo et al 2012; but see Morey et al 2012). As T allele carriers are assumed to exhibit a higher expression of FKBP5 and, thereby, a slower cortisol recovery after challenge, the observed effect on amygdala activity and volume may be related to enhanced cortisol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Exaggerated amygdala activation has been suggested to represent a common neurobiological pathway for stress-related disorders, such as depression and anxiety disorders (Drevets et al 2008;Etkin and Wager 2007). Likewise, in the majority of studies, larger amygdala volumes have been observed in depression (Altshuler et al 1998;Bremner et al 2000;Lange and Irle 2004;Tebartz van Elst et al 1999;van Eijndhoven et al 2009;Vassilopoulou et al 2013), (but see Hastings et al 2004;von Gunten et al 2000 for opposite findings) and PTSD (Kuo et al 2012; but see Morey et al 2012). As T allele carriers are assumed to exhibit a higher expression of FKBP5 and, thereby, a slower cortisol recovery after challenge, the observed effect on amygdala activity and volume may be related to enhanced cortisol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the cingulate cortex have also been observed by many authors. Among these, a smaller anterior cingulate (or Brodmann Area 24: BA24) was observed in depressed patients when compared to controls 9,24,25 and altered activity has also been reported. [26][27][28] Brodmann area 29 (BA29) or posterior cingulate, has been associated mainly to response to antidepressant treatment with changes in metabolic response associated with the different treatments.…”
Section: Introductionmentioning
confidence: 95%
“…5 Neuroimaging studies have produced a substantial body of knowledge about alterations of the limbic system in mood disorders. In the amygdala, alterations in cerebral blood flow and metabolism, 6 asymmetry of amygdalar volumes, 7 as well as smaller [8][9][10] and larger volumes [11][12][13][14] have been observed in depressed subjects when compared with normal controls. In the hippocampus, volumetric analysis studies have also revealed reduced volumes in subjects suffering from major depression in some, 7,11,[14][15][16][17][18][19][20] but not all studies 10,[21][22][23] comparing depressed patients versus controls.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported gray matter reductions in the subgenual gyrus (BA24 sg ) in patients with MDD when compared to age-and sex-matched controls (Botteron et al, 2002;Drevets et al, 1997;Hastings et al, 2004; but see, Brambilla et al, 2002;Bremner et al, 2002 for negative findings). In contrast to Bremner et al (2002) and Pizzagalli et al (2004), who found no differences in BA25 or in BA32 (Bremner et al, 2002) volume between MDD patients and healthy controls, Coryell et al (2005) subsequently reported a reduction in left subcallosal gyrus volume in patients with MDD relative to controls.…”
Section: Introductionmentioning
confidence: 99%